Polyploidy induction in Physalis alkekengi - Gustavo C Santos; Felipe P Cardoso; Adalvan Daniel Martins; Filipe A Rodrigues; Moacir Pasqual; Paulo Cossani; José Magno Queiroz Luz; Renata A L S Rezende; Joyce Dória Rodrigues Soares (Bioscience Journal, 2020)
Physalis alkekengi is an ornamental plant that can also be used as a medicinal plant due to its anti-inflammatory, bactericidal, antitumor and fungicidal properties. Polyploidization can be an important tool in the genetic improvement of this species. The objective this work was to obtain tetraploids in vitro and to evaluate the phytotechnical traits of P. alkekengi. For this, nodal segments of P. alkekengi var. Franchettii were inoculated into petri dishes containing 100 ml of MS medium supplemented with colchicine at concentrations 0; 0.04; 0.08; 0.12; and 0.16% and kept in the dark for 24 and 48h. After the respective treatment periods with colchicine the segments were inoculated into test tubes. The tetraploids were identified by flow cytometry and classical cytogenetics. In vitro seedlings were measured: root length, nodal segment length, leaflet number and total leaf area. In the acclimatization phase, the area of ​​the second leaf and total leaf, petiole radius, stem length, fruit weight with calyx, without calyx, fruit diameter, number of seeds and brix of the pulp were evaluated. Chlorophyll a, chlorophyll b, total chlorophyll, total carotenoid, total chlorophyll / total carotenoid ratio and chlorophyll a / b ratio were also estimated. The treatment that most produced tetraploid seedlings was with 0.08% colchicine per 24h. No significant difference was observed in 7 (seven) variables, these being all variables of photopigments, stem diameter (steam) and brix. In general, diploid (2x) plants were better in 9 (nine) while tetraploid seedlings were better in 6 (six) of the phytotechnical variables. It was concluded that the MS medium supplemented with 0.08% colchicine for 24 h allowed P. alkekengi tetraploides to be obtained with better phytotechnical qualities.